Penggunaan Smartphone Pada Petani Remaja di Desa Leworeng Kec.donri-donri Kab.Soppeng - ., Mauliadi Ramli (PREDESTINASI, 2022)
AbstractAbstract. The development of science and technology is something that cannot be avoided, changes in all sectors are the impact of this, the education sector, social politics and the economy, one example of the economic sector is the use and increase in gadget users, in this case smartphones, which have even become the basic needs of every individual in all circles, one of which is among young farmers in Leworeng Village, Donri-Donri District, Soppeng Regency. This study aims: To determine the use of Smartphones among adolescent farmers. The research method used is descriptive qualitative method. The data sources were selected by purposive sampling. Data was collected by means of observation and interviews. The results showed that: the habit of using Smartphones among adolescent farmers in Leworeng Village was divided into several things, namely; for the purposes of farmer groups, in this case rice motorcycle taxis, entertainment facilities where they can play games and access YouTube and Facebook, as well as online shopping facilities through the marketpalce feature on smartphones. Keywords: Farmer, teenager, Smartphone, Farmer's Child.